Antibacterial Activity of Ethanol Extracts of the Zingiber zerumbet (L.) Smith Rhizome Against Salmonella sp. - Rahayu, Imbang Dwi; Widodo, Wahyu; Prihartini, Indah; Winaya, Aris (INSIST, 2019)
The study aimed at investigating the antibacterial activity of ethanol extracts of the lempuyang Gajah (Zingiber zerumbet (L.) Smith) rhizome against S. enteridis ATCC 31194 and S. typhimurium  ATCC 23564. An experimental method was employed for testing the antibacterial activity, with a completely randomized design (CRD) of factorial patterns. Factor I, ethanol concentrations which consisted of 45%; 70% and 95%, while factor II was the concentration of extracts, i.e 0%; 2.5%; 5%; 7.5% and 10%. The results showed that extraction with 45% and 70% ethanol, Z. zerumbet contained alkaloids, tannins, terpenoids, and saponins; however, the-95%-ethanol did not result any saponins, but flavonoids instead. Meanwhile, the chromatogram patterns of all extracts showed zerumbone is a dominant compound. It was concluded that the Z. zerumbet (L.) Smith extracts with 95% ethanol solvent, and 10% concentration had the highest antibacterial properties against S. enteritidis.